OPTIMALISASI KINERJA MGMP DENGAN METODE BIMBINGAN TERPADU DALAM UPAYA PENINGKATAN KOMPETENSI GURU - Tigor Siahaan (JURNAL PENA EDUKASI, 2019)
Abstract: Student learning outcomes by applying mastered MGMP activities on a guided basis becomes increasing. Before carrying out the Automotive Engineering average value action is 60.25 and the standard deviation is 5.02. After taking action on the first cycle the average student learning outcomes are 72.00 and the standard deviation is 4.53. Likewise in the second cycle the average student learning outcomes become increased, namely 76.00 and standard deviation 3.50. Before the action is done the average category of learning outcomes is in the low category with a completeness level of 37.5%. In the first cycle after the action learning outcomes are in the medium category with a completeness level of 72.00%. In the second cycle after further action was taken as a result of reflection the first cycle of learning outcomes was in the medium category with a completion rate of 76.00%.Keyword: Teacher Competence, Integrated GuidanceAbstrak: Hasil belajar siswa dengan menerapkan menguasai kegiatan MGMP secara terbimbing menjadi meningkat. Sebelum dilaksanakan tindakan nilai rata-rata Teknik Otomotif adalah 60,25 dan standar deviasi 5,02. Setelah dilakukan tindakan pada siklus I nilai hasil belajar siswa rata-ratanya adalah 72,00 dan standar deviasi 4,53. Demikian pula pada siklus II rata-rata hasil belajar siswa menjadi meningkat yaitu 76,00 dan standar deviasi 3,50. Sebelum dilakukan tindakan kategori rata-rata hasil belajar berada pada kategori rendah dengan tingkat ketuntasan 37.5 %. Pada siklus I setelah dilakukan tindakan hasil belajar berada pada kategori sedang dengan tingkat ketuntasan 72,00 %. Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil refleksi siklus I hasil belajar berada pada kategori sedang dengan tingkat ketuntasan 76,00 %.Kata kunci: Kompetensi Guru, Bimbingan Terpadu